Ghana : Sixth and Seventh Reviews Under the Three-Year Arrangement Under the Extended Credit Facility and Requests for Waiver of Nonobservance of Performance Criteria and Extension of the Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report, 2012)
The Sixth and Seventh Reviews under the three-year arrangement of the Extended Credit Facility observed that te Ghanaian economy performed well in 2011, but risks to macroeconomic stability have risen recently. Even though debt management capacity and policies have been strengthened, progress has been slow in investment planning. The authorities, to maintain growth, have adopted policies to respond, and program objectives have been set within reach. The authorities have requested for a waiver of nonobservance of performance criteria and an extension of the arrangement.